This or that? Managerial responses to competing priorities in organizations - Mariano, Stefania (2025)
Purpose This study aims to examine current scholarly literature on how managers address competing priorities in organizations. It consolidates existing contributions into an organizing framework to guide future research. Design/methodology/approach A systematic literature review was used to identify, select and review peer-reviewed articles from Scopus, ABI/Inform and ScienceDirect (Elsevier) databases over 4 decades. Findings This study identified the antecedents and conditions of competing managerial priorities in organizations and highlighted potential managerial responses, including addressing, altering, converging, postponing and neglecting. Originality/value This study represents a primary reference in management and organizational studies for scholars interested in competing priorities in organizations. It discusses the implications for scholarly theories and managerial practices and provides an agenda for future research.